2012
DOI: 10.21059/buletinpeternak.v35i2.595
|View full text |Cite
|
Sign up to set email alerts
|

Kinerja Kambing Bligon Yang Dipelihara Peternak Di Desa Giri Sekar, Panggang, Gunungkidul

Abstract: <p>This study was conducted to evaluate performances of Bligon goats kept by farmers at Giri Sekar village, Panggang sub-district, Gunungkidul as basic information for establising the village breeding centre program. The research was conducted for three months, starting from October to December 2010, located at Purwo Manunggal farmers’ group, Jerukan, Giri Sekar village, Panggang, Gunungkidul, Yogyakarta. Twenty farmers were involved during the study to be interviewed, while their goats were measured reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 3 publications
0
7
1
7
Order By: Relevance
“…Postpartum mating in this group is longer than Sundari Aprilinda et al (2016) that reported postpartum mating in PE goat is 2.69 ± 0.48 months. The comparison of other reports that postpartum mating ranged of 45 -180 days for Bligon goats (Murdjito et al, 2011) and 122 days for Bligon goats (Rustadi, 2008).…”
Section: Weaning Age Days Open and Post Partum Matingmentioning
confidence: 62%
See 1 more Smart Citation
“…Postpartum mating in this group is longer than Sundari Aprilinda et al (2016) that reported postpartum mating in PE goat is 2.69 ± 0.48 months. The comparison of other reports that postpartum mating ranged of 45 -180 days for Bligon goats (Murdjito et al, 2011) and 122 days for Bligon goats (Rustadi, 2008).…”
Section: Weaning Age Days Open and Post Partum Matingmentioning
confidence: 62%
“…Days Open is the length of time after the doe has given birth to the pregnant again. Murdjito et al (2011) stated that Days Open (DO) is the length of time the goats after giving birth until they are pregnant again normally between 2-3 months. The empty duration shows the time interval between giving birth and conception again (Hafez and Hafez 2008. Days Open of PE goats in this study were for 3 months (90 days), this condition was longer compared to the results of Syukur's research (2006) (Hafez and Hafez 2000).…”
Section: Weaning Age Days Open and Post Partum Matingmentioning
confidence: 99%
“…Interval kelahiran hasil penelitian Murdjito et al(2011) rata-rata 8,53 bulan dengan kisaran 7 -12 bulan. Menurut.…”
Section: Jarak Beranak (Kidding Interval )unclassified
“…Hasil penelitian terhadap PPM kambing PE dan Bligon di kedua wilayah masih masuk dalam kisaran normal, sebagaimana telah diteliti pada kambing Bligon di wilayah Gunungkidul yang memiliki PPM 45 -180 hari dengan ratarata 95 hari (Murdjito et al, 2011) dan 122 hari pada kambing Bligon (Rustadi, 2008). PPM menunjukkan kemampuan seekor induk untuk timbulnya keinginan kawin setelah beranak.…”
Section: Post Partum Mating (Ppm)unclassified
See 1 more Smart Citation